Sarcopenia in cancer: Risking more than muscle loss. (December 2020) - Anjanappa, Milan; Corden, Michael; Green, Andrew; Roberts, Darren; Hoskin, Peter; McWilliam, Alan; Choudhury, Ananya
Abstract: Sarcopenia is characterised by progressive and extensive skeletal muscle degeneration and is associated with functional decline. Sarcopenia has primary and secondary aetiology, arising as a result of the ageing process or through chronic cytokine-mediated inflammation (associated with health conditions including cancer), respectively. Diagnosis of sarcopenia is dependent upon detection of reduced skeletal muscle strength, mass and performance. A combination of non-radiological and radiological methods can be used to assess each of these in turn to accurately diagnose sarcopenia. Sarcopenia is known to adversely affect outcomes of patients with various forms of cancer. Early identification of sarcopenia is imperative in improving patient care and overall prognosis. Various interventions, such as resistance exercise, nutritional support, and amino acid and vitamin supplementation have shown promise in the management of sarcopenia. However, further insight into novel interventions and indeed, assessment of the benefits of management of sarcopenia in terms of survival, are required to better support cancer patients.